Critical Role of AKT Protein in Myeloma-induced Osteoclast Formation and Osteolysis - Cao, Huiling (American Society for Biochemistry and Molecular Biology, 2013)
Abnormal osteoclast formation and osteolysis are the hallmarks of multiple myeloma (MM) bone disease, yet the underlying molecular mechanisms are incompletely understood. Here, we show that the AKT pathway was up-regulated in primary bone marrow monocytes (BMM) from patients with MM, which resulted in sustained high expression of the receptor activator of NF-κB (RANK) in osteoclast precursors. The up-regulation of RANK expression and osteoclast formation in the MM BMM cultures was blocked by AKT inhibition. Conditioned media from MM cell cultures activated AKT and increased RANK expression and osteoclast formation in BMM cultures. Inhibiting AKT in cultured MM cells decreased their growth and ability to promote osteoclast formation. Of clinical significance, systemic administration of the AKT inhibitor LY294002 blocked the formation of tumor tissues in the bone marrow cavity and essentially abolished the MM-induced osteoclast formation and osteolysis in SCID mice. The level of activating transcription factor 4 (ATF4) protein was up-regulated in the BMM cultures from multiple myeloma patients. Adenoviral overexpression of ATF4 activated RANK expression in osteoclast precursors. These results demonstrate a new role of AKT in the MM promotion of osteoclast formation and bone osteolysis through, at least in part, the ATF4-dependent up-regulation of RANK expression in osteoclast precursors.